Pengaruh Pemahaman Ekonomi, Gaya Hidup, dan Modernitas terhadap Rasionalitas Konsumsi Mahasiswa Dimediasi Self- Efficacy Financial - Ulum, Bahrul (Lembaga Yasin AlSys, 2025)
The objectives of this study are to: 1) examine the impact of economic understanding on consumption rationality; 2) determine the influence of lifestyle on consumption rationality; 3) assess the effect of modernity on consumption rationality; and 4) evaluate the partial and simultaneous effects of economic understanding, lifestyle, and modernity on consumption rationality through financial self-efficacy. This study employs Warp PLS analysis and explanatory correlational research methods. The research population consists of students from the Faculty of Islamic Economics and Business, Class of 2021. The sampling design used is random sampling, involving 99 respondents. Warp PLS 8.0 was utilized to analyze data and represent the sample, covering all members of the Class of 2021 in the Faculty of Islamic Economics and Business. The research findings are as follows: Economic understanding has a positive and significant effect on consumption rationality through financial self-efficacy, with a coefficient of 0.137*. Lifestyle has a positive and significant effect on consumption rationality through financial self-efficacy, with a coefficient of 0.113*. Modernity has a positive and significant effect on consumption rationality through financial self-efficacy, with a coefficient of 0.053*. These results indicate that economic understanding, lifestyle, and modernity significantly contribute to students' consumption rationality when mediated by financial self-efficacy.